Decorate your shoes : create one-of-a-kind footwear - Berendse, Annemart (American Quilter's Society, 2012)
"Author provides 11 projects for seven shoe types and explains how to mark on leather, vinyl, and canvas. Embellish and decorate shoes with fabric markers and paints"--Provided by publisher.